OBSTACLES FACED BY PRE - SERVICE ENGLISH TEACHERS DURING TEACHERS’ PROFESSIONAL EDUCATION PROGRAM (PPG) - Warahmah, Mawaddah; Daud, Afrianto; Novitri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2021)
The Indonesian government has issued new rules to prepare pre-service teachers to be professional teachers in the future by asking them to attend additional education named Teachers Professional Education Program (locally known as Pendidikan Profesi Guru, henceforth PPG). This case study aimed to identify the obstacles experienced by pre-service English teachers in FKIP Universitas Riau during the PPG program and the Teaching Practicum (PPL) as a part of the PPG program. This qualitative research involved 10 alumni of the Subsidized PPG English Education Department. Focus Group Discussion was used to collect data from the participants. The data obtained were analyzed using Miles and Huberman’s (1984) thematic analysis and referred to the three procedures introduced by Flick (2002) i.e., open coding, axial coding and selective coding with the help of the NVivo 12 software. The findings showed seven emerging obstacles faced by the pre service English teachers during PPG. There were one (1) obstacle found at the first-semester theory program in PPG, and six (6) obstacles found at the second-semester practicum program in PPG known as PPL, which can be used as an input for further PPG students to prepare themselves both physically and mentally when participating in PPG as well as that for the development of a better PPG system in the future used by the government.